2016
DOI: 10.22631/rr.2016.40681
|View full text |Cite
|
Sign up to set email alerts
|

Can pregnancy induce relapse in systemic lupus erythematosus (SLE)?

Abstract: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease which mostly affects women of reproductive age. We evaluated the impact of pregnancy on maternal/fetal health, the pattern of organ involvements and the fare-up risk. In a retrospective study we studied the thirty-year medical records of patients between 1976-2005. Maternal, neonatal and infantile health data was retrieved. Incidence of flare-ups, pattern of organ involvements and the outcome of pregnancy was analyzed. We studied 155 pregnancie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In the previous studies, abortion has been one of the most common pregnancy outcomes in women with SLE. This complication in study of Yuen et al [10] and Parastandechehr et al [11] were reported 19.5% and 19%, respectively. Clowse and colleagues were founded that the activity of SLE during pregnancy led to a threefold increase in spontaneous abortion [12].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In the previous studies, abortion has been one of the most common pregnancy outcomes in women with SLE. This complication in study of Yuen et al [10] and Parastandechehr et al [11] were reported 19.5% and 19%, respectively. Clowse and colleagues were founded that the activity of SLE during pregnancy led to a threefold increase in spontaneous abortion [12].…”
Section: Discussionmentioning
confidence: 83%
“…Disease activity was estimated based on the systemic lupus erythematosus disease activity index (SLEDAI). Patients were categorized into three groups, according to SLEDAI score: remission (6>), mild to moderate activity [6][7][8][9][10][11][12] and high activity (>12). The medical records of patients were comprehensively reviewed to collect demographic, clinical and laboratory data.…”
Section: Methodsmentioning
confidence: 99%
“…During lupus pregnancies, there is an increased risk of maternal and fetal morbidity and mortality, but a stable disease prior to conception can act as predictor of a good outcome [38]. The onset of new symptoms or signs as arthritis, discoid or subacute cutaneous lupus lesions, oral ulcers, vasculitis, polyserositis, lymphadenopathy, positive direct Coombs, myocarditis, pneumonitis, proteinuria, leucopenia, thrombocytopenia, complement consumption or raised anti-DNA antibody expression must arise the suspicion about an ongoing lupus flare [12,38].…”
Section: Lupus Flarementioning
confidence: 99%
“…During a healthy pregnancy, complement levels are usually raised, as it acts as acute phase reactant [31]. So, normal or lower range of complement suggests serum consumption due inflammatory process [38]. The coexistence of hypocomplementemia and high SLE activity usually predicts a poor pregnancy outcome.…”
Section: Lupus Flarementioning
confidence: 99%
See 1 more Smart Citation